Association Between Uric Acid Levels and Stenosis Severity in Patients With and Without Renal Insufficiency - M Saugi Abduh; Muh Adytia Prasada; Ahmad Umar Alfaruq; Dimas Irfan Nabih (Journal of Health and Nutrition Research, 2026)
Hyperuricemia is associated with an increased risk of atherosclerosis and coronary stenosis, particularly in the presence of renal insufficiency. However, the independent relationship between serum uric acid levels and the severity of coronary stenosis, when stratified by renal function, remains poorly understood. This study aimed to evaluate the association between serum uric acid concentrations and the extent of coronary stenosis in patients with and without renal insufficiency. A cross-sectional study was conducted on 853 patients diagnosed with acute coronary syndrome (ACS) who underwent coronary angiography. Elevated uric acid was defined as ≥ 7.1 mg/dL, while renal insufficiency was defined as an estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73 m². The associations between variables were analyzed using Chi-square tests and logistic regression models. The 853 patients, 386 (45.3%) presented with renal insufficiency. In the overall cohort, elevated uric acid levels were significantly associated with coronary stenosis of 50% or greater (p = 0.005). However, upon subgroup analysis, this association lost statistical significance in both the renal insufficiency (p = 0.319) and non-renal insufficiency (p = 0.154) groups. Conversely, traditional cardiovascular risk factors—specifically advanced age (p < 0.001), male sex (p < 0.001), and smoking history (p = 0.008)—remained significantly associated with coronary stenosis across both subgroups. While elevated serum uric acid levels correlate with coronary stenosis in the general ACS population, this relationship does not remain independently significant when patients are stratified by renal function. Traditional risk factors, such as age, sex, and smoking, serve as more robust predictors for the progression of coronary stenosis.